2015
DOI: 10.1371/journal.pone.0130268
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Body Composition and Walking Capacity in Severe Obesity

Abstract: BackgroundObesity is associated with mobility reduction due to mechanical factors and excessive body fat. The six-minute walk test (6MWT) has been used to assess functional capacity in severe obesity.ObjectiveTo determine the association of BMI, total and segmental body composition with distance walked (6MWD) during the six-minute walk test (6MWT) according to gender and obesity grade.SettingUniversity of São Paulo Medical School, Brazil; Public Practice.MethodsFunctional capacity was assessed by 6MWD and body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
(51 reference statements)
1
12
0
2
Order By: Relevance
“…In addition, almost all previous studies involving the 6 MWT have been performed in samples predominantly composed of obese women, who have very different performance from that observed in obese men during submaximal exercise [ 3 , 6 , 11 , 19 , 21 ]. Similar to Wooldridge et al [ 4 ], Vanhelst et al [ 22 ], and Hulens et al [ 23 ], we observed that BMI was one of the most important variables in the reference equation for the 6 MWD of obese subjects, which is not surprising because excess weight increases the workload and affects walking due to trunk oscillation and the increased distance between the feet [ 2 ]. Age was also a variable that was included in the reference equation for the 6 MWD in this population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, almost all previous studies involving the 6 MWT have been performed in samples predominantly composed of obese women, who have very different performance from that observed in obese men during submaximal exercise [ 3 , 6 , 11 , 19 , 21 ]. Similar to Wooldridge et al [ 4 ], Vanhelst et al [ 22 ], and Hulens et al [ 23 ], we observed that BMI was one of the most important variables in the reference equation for the 6 MWD of obese subjects, which is not surprising because excess weight increases the workload and affects walking due to trunk oscillation and the increased distance between the feet [ 2 ]. Age was also a variable that was included in the reference equation for the 6 MWD in this population.…”
Section: Discussionsupporting
confidence: 87%
“…Obesity hinders walking and is therefore an important component of functional limitation, which can be caused by a sedentary lifestyle and the numerous adverse effects of excess weight [ 1 , 2 ]. Obese individuals have a lower exercise capacity not only because walking is a weight-bearing activity but also because these individuals have significant comorbidities [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Ben Saad et al ( 22 ) showed that when BMI is included in their final reference equation, 6MWD decreased 5.27 m for each increase of 1 unit in BMI. Obese subjects adapt to their higher body mass by decreasing walking speed and they tend to oscillate the trunk while walking and increase the distance between the ankles when stopping, to compensate for their extra body mass ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a chronic disease that has reached epidemic proportions in children and adults; it is currently the fifth leading risk factor for mortality [ 1 ]. According to the World Health Organization (WHO), obesity has been growing at an alarming rate in the last decade and is becoming a significant public health problem [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%